Strategic Alignment of the Judiciary with the Sustainable Development Goals of Agenda 2030 - Camelo, Odislene Gonçalves; Pila, Adriano Donizete (JRG Journal of Academic Studies, 2023)
The study in question focuses on the analysis of the relationship between the Sustainable Development Goals (SDGs) and the strategic projects carried out by state courts in Brazil, using a bibliographical methodology. The results highlight a significant alignment between the SDGs and the strategic projects in state courts such as Acre, Rio Grande do Sul, Paraíba, and Paraná, indicating a trend for these courts to integrate sustainability issues into their practices. Conversely, a gap is demonstrated in the state courts of Alagoas and Goiás, where strategic projects tend to neglect environmental and social aspects. This scenario points to the need for a review of the strategies and practices adopted, ensuring that the actions of the courts are in line with the principles of sustainable development.